Penggunaan Gadget dan Pengaruh Buruknya Terhadap Perkembangan Bahasa Anak (Suatu Kajian Psikolinguistik) - Imaratul Ulwiyah (Mathematics Education Study Program, 2025)
This case study is held to knowing the side effects of using gadget by children ages 5-8. In our daily lifes, gadget can be assistant in doing many things such as communication equipments, browsing facts or knowledges, entertainment or even as life style. If gadget used by children without special supervision, it will give negative effect for their language development. It is called ‘mistake’. This kind of mistake will happen if the contents that they watched full of impolite words. Children will directly imitate what they’ve heard without considering the meaning or its congruity. As a result, it will be constantly influence children’s language development.